2014
DOI: 10.1016/j.psychres.2014.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Differential hedonic experience and behavioral activation in schizophrenia and bipolar disorder

Abstract: The Kraepelinian distinction between schizophrenia (SZ) and bipolar disorder (BP) emphasizes affective and volitional impairment in the former, but data directly comparing the two disorders for hedonic experience are scarce. This study examined whether hedonic experience and behavioral activation may be useful phenotypes distinguishing SZ and BP. Participants were 39 SZ and 24 BP patients without current mood episode matched for demographics and negative affect, along with 36 healthy controls (HC). They comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 64 publications
3
22
1
Order By: Relevance
“…Items only reflect physical anhedonia as the authors believed this would result in more homogenous and interpretable results. The scale was validated using a student population, and extended, to the best of our knowledge, only to schizophrenia and bipolar disorder psychiatric populations (Gard et al, 2007; Tso et al, 2014). Although the authors report that items were developed to avoid cultural bias, certain questions could still be seen as culture specific (“When I'm on my way to an amusement park, I can hardly wait to ride the roller coasters”).…”
Section: Clinical Methodsmentioning
confidence: 99%
“…Items only reflect physical anhedonia as the authors believed this would result in more homogenous and interpretable results. The scale was validated using a student population, and extended, to the best of our knowledge, only to schizophrenia and bipolar disorder psychiatric populations (Gard et al, 2007; Tso et al, 2014). Although the authors report that items were developed to avoid cultural bias, certain questions could still be seen as culture specific (“When I'm on my way to an amusement park, I can hardly wait to ride the roller coasters”).…”
Section: Clinical Methodsmentioning
confidence: 99%
“…Of the 23 studies that included schizophrenia and control samples, 11 have found lower anticipatory pleasure in individuals with schizophrenia than controls [6769, 9, 7075, 52]; however, these findings may be specific to patients with severe negative symptoms [76]. Ten studies found no group differences in anticipatory pleasure [7779, 39, 8085].…”
Section: Anticipatory Affect Affective Forecasting and Prospectionmentioning
confidence: 99%
“…Ten studies found no group differences in anticipatory pleasure [7779, 39, 8085]. Eight studies found lower consummatory pleasure in schizophrenia patients than controls [78, 71, 72, 74, 8183, 75], while 12 found no group differences in consummatory pleasure [52, 85, 84, 80, 39, 79, 73, 70, 9, 69, 77, 67]. Eleven studies have reported group means for the TEPS subscales in patient and control groups, which provide evidence for numerically lower consummatory and anticipatory pleasure in schizophrenia: Schizophrenia anticipatory = 4.17; Control anticipatory = 4.54; Schizophrenia consummatory = 3.99; Control consummatory = 4.35.…”
Section: Anticipatory Affect Affective Forecasting and Prospectionmentioning
confidence: 99%
“…People with SZ (Horan et al, 2008; Kring and Moran, 2008; Myin-Germeys et al, 2000; Oorschot et al, 2013) or BD (Gruber et al, 2011; Tso et al, 2014) report a higher frequency of negative emotions. This evidence is contrary to the longstanding reports of emotional abnormalities in SZ, which are largely based on the appearance of a lack of emotion in schizophrenia (e.g., flat affect and anhedonia, Bleuler, 1950; Kraeplin, 1919; Kring and Moran, 2008; Tremeau, 2006).…”
Section: Introductionmentioning
confidence: 99%